The Conditions for the Possibility of Testimony and Affirmative Ethics in The Rose of Lebanon - Mishmar, Tamar (MiKAN, 2016)
The Rose of Lebanon, Lea Aini’s autobiographical novel, is a work of multiple and tightly linked traumas: the trauma of the Holocaust of the Salonika Jews, borne by Isaac, the narrator’s father, and the trauma of the sexual abuse endured at the hands of this father by his daughter, Lea. These two traumas cross paths in the face of a third trauma, that of the First Lebanon War, which has no bearer, as its subject, a soldier who chose to attempt suicide rather than fight the war, lies in a vegetative state. The narrator in The Rose of Lebanon, a witness who is also a survivor, becomes the point of intersection for these three traumas. The narrative choice of multiple traumas allows us to reconsider, in unexpected ways, the possibility and the boundaries of testifying about trauma. This in turn leads us to reflect on what the article takes to be the fundamental issue of this field, namely the power of literature to function as the carrier of historical memory and its ethical expression. Hence, testimony is analyzed as an ethical situation of inter-subjective subject construction and of the affirmation of life. Moreover, the article makes clear that the novel builds a meaningful connection between the aesthetical, the ethical and the political in the face of the First and Second Lebanon Wars.